Implementation of the Merdeka Curriculum in Strengthening the Profile of Pancasila Students in Class IV of SD Negeri 8 Juara Barat - Sari, Emi Liana; Musafir, Musafir; Mulyono, Ana (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to determine teachers' strategies in implementing the Merdeka curriculum in strengthening the Pancasila profile which teachers carry out in order to form character in students and the obstacles teachers face in strengthening the values of the Pancasila profile. There are phenomena or advantages of schools, namely; there is a character building program for students. The subject of this research is strengthening Pancasila values in students in the dimension of faith, devotion to God Almighty in class IV students at SD Negeri 8 Juara Barat. The method used in this research is a qualitative method with a descriptive approach. And using technical data analysis which includes observation, interviews and documentation. The results of conformity in the field concluded that the implementation of the Merdeka curriculum in strengthening the profile values of Pancasila was carried out through daily refraction and spontaneous refraction or replay. The refraction carried out can help develop students' character in accordance with the dimensions of the Pancasila profile elements. However, with the strategy implemented, there are several inhibiting factors experienced by teachers, namely; The number of obese students or classes, lack of use of learning media, family environment, and lack of teacher cooperation between students' parents. So these factors become obstacles for teachers in instilling character values in students in accordance with the Pancasila profile.